Three-element control system manipulation in steam generation for palm oil industry - Chew, I.; Wong, F.; Bono, A.; Wong, Kiing-Ing (American Scientific Publishers, 2017)
This paper presents the performance flow control of feedwater inflow to the boiler drum in respond to the changes of steam load at the outlet of boiler drum. The changes of load consequences swell and shrink effect, which drastically reduces the efficiency of boiling process besides endangers the boiler facility. PID controller is proposed for controlling consistency of feedwater inflow for stability of water level in the boiler drum. In this paper, Process Control Simulator is used to justify the controller performance resulted from applied control actions. At first, open loop test is conducted for developing FOPDT model of the process. This is followed by calculating the correlation PID values with formulas from Cohen-Coon method. The optimized system performance is achieved through PID refined tuning that produces non-oscillating output response in restoring process variable towards setpoint value. Overall, the experimental test provides insight for justifying the trends of controller action upon various steam loads that has been measured in the real operation of boiler.